Bonemarrow Fibrosis Grade; A Useful Prognostic Marker in Myeloproliferative Neoplasms - Asghar, Muhammad Bilal; Malik, Hamid Saeed; Rafique, Nabila; Bozdar, Manzar; Mahmood, Rafia; Ali, Intzar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the prognostic significance of bone marrow fibrosis grade in predicting the outcome of myeloproliferative neoplasms.Study Design: Prospective longitudinal study.Duration and Place of Study: Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jun 2021 to May 2022.Methodology: A total of 114 patients with myeloproliferative neoplasms were included. Under aseptic conditions, a bone marrow aspiration and a Trephine biopsy were obtained. Following processing, the samples underwent staining with Hemotoxylin and Eosin and Reticulin. The WHO bone marrow fibrosis grading system was used to grade the fibrosis. Clinical findings and haematological parameters documented at initial diagnosis were compared with one-year interval follow-up counts.Results: Out of a total 114, 72(63.2%) were male and 42(36.8%) were female. Generalised weakness and pallor were documented in 51(44.7%) and 27(23.7%), respectively. While splenomegaly and/or hepatomegaly were detected in 61(53.5%) and 27(23.7%), respectively, 16(14.9%) transformed into other MPNs and 3(2.6%) into acute leukemia. People who had higher levels of MF-2 and MF-3 reticulin fibrosis had the worst prognosis when it came to peripheral blood cytopenias, disease progression, and transformation.Conclusion: Myeloproliferative neoplasms are very different from one another in terms of how they look and behave. As the grade of fibrosis rises, there is a high chance that the disease will progress to myelofibrosis or change into acute leukaemia, both of which are very bad for overall survival.